Aplikasi Maqashid Ekonomi Syariah Ibnu Asyur Pada Sistem Penggunaan Iklan Payper Click Melalui Facebook Adsense - Nurul Huda; Eko Arif Cahyono (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2023)
The Pay Per Click (PPC) advertising mechanism indicates that there is an element of gharar because in the transaction there is a ju'alah pillar that is not fulfilled, namely the unclear amount of wages (ju'lu) that the advertiser (ja'il) must give to Facebook Ads (maj'ul-lahu), where the ambiguity is because the PPC system advertising fee is determined based on the number of audiences who click on the ad links, even though any party cannot know how many audiences have been reached before the advertising period ends. Meanwhile, Gharar is one of the elements that can cancel economic transactions. This research method uses descriptive-qualitative data collection using observation, interviews, and documentation. After conducting research, the gharar that occurs in PPC transactions is not significant and tolerance must be given so that maqashid sharia in the economic field in the form of rawaj al-mal is realized so that economic growth becomes high, income distribution in the community and poverty reduction